2013
DOI: 10.1007/s12282-013-0483-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical trial of metronomic chemotherapy with combined irinotecan and tegafur–gimeracil–oteracil potassium in metastatic and recurrent breast cancer

Abstract: Metronomic chemotherapy with combined irinotecan and TS-1 was effective in MRBC patients. Adverse effects were mild and the regimen was safely administered without identifying UGT1A1 polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Munzone et al summarized some ongoing clinical trials and the forthcoming results may be helpful [2,15]. Meanwhile, according to the principles of precision medicine, prognosis factors such as vascular endothelial growth factor (VEGF), serum HER-2 and EGFR, endothelial nitric oxide synthase (eNOS), thrombospondin-1 (THBS-1), circulating endothelial cells (CECs), and gene polymorphism should be considered for patient selection to standardize MCT [18,26,28,32,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Munzone et al summarized some ongoing clinical trials and the forthcoming results may be helpful [2,15]. Meanwhile, according to the principles of precision medicine, prognosis factors such as vascular endothelial growth factor (VEGF), serum HER-2 and EGFR, endothelial nitric oxide synthase (eNOS), thrombospondin-1 (THBS-1), circulating endothelial cells (CECs), and gene polymorphism should be considered for patient selection to standardize MCT [18,26,28,32,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Via steps of screening the title and reading the abstract, 5 studies were identified (Frasci et al, 2005;Stathopoulos et al, 2005;Moulder et al, 2008;Lee et al, 2013;Otsuka, et al, 2013). These studies had been carried out in China, Japan, Korea, Europe and the USA.…”
Section: Resultsmentioning
confidence: 99%
“…When irinotecan is used for treating patients with MBC, several studies should be mentioned. One is a Japanese study comprised 40 patients aged 35-79 years (Otsuka et al, 2013). In this study, Irinotecan was administered at 60 mg/m 2 , and was infused on days 1, 8, and 15 for every 4 weeks, and accompanied by TS-1 (at 80 mg/m 2 /day orally on days 3-7, 10-14, and 17-21 every 4 weeks) (Otsuka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irinotecan (CPT-11), a water-soluble derivative of camptothecin, is a highly effective chemotherapeutic agent which has been widely used in clinical practice to treat colon (Mukai et al, 2009), gastric (Takiuchi, 2009), pancreatic (Stathopoulos et al, 2003), and varieties of other cancers (Mrozek et al, 2008; Otsuka et al, 2015; Trafalis et al, 2016) through the inhibition of DNA topoisomerase I. However, dose-limiting toxicities myelosuppression, neutropenia, and gastrointestinal (GI) toxicity, particularly severe late-onset diarrhea, compromise the efficacy and safety of irinotecan-based chemotherapy (Kakolyris et al, 2001; Benson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%